An approach to stimulate population proliferation and spread of Trichoderma harzianum in soil ecosystem - SITANSU PAN*, SHAONLI BOSE and (Indian Phytopathology, 2009)
Proliferation of the antagonist was tested against three soil types viz., clay, sandy and loam soil by inoculating spores form of Trichoderma grown on wheat bran + mustard cake formulation. Mycelial preparation stood better than spore preparation in each case and among the three soil types loam soil performed the best in terms of c.f.u. / g of soil. In another set of experiment where different forms of T. harzianum i.e. mycelium without bran, mycelium followed by bran, mycelium mixed with bran and mycelium grown on bran was mixed with soil (loam) to determine the best form of the formulation it was found over 3 weeks of observation that mycelium grown on bran performed best (8 x 106 c.f.u. /g of soil population) than the others. Least population recorded in case of mycelium without bran. Radial spread of the antagonist was found to vary with type of soil. However, the population density was very low in non-sterilized soil counting only 19.2 x 103 c.f.u. /g of soil. At 250 C soil temperature T. harzianum grew very fast and highest population (91.4 x 103 c.f.u. /g) build up occurred at 25 cm. In all the treatments population declined with distance from inoculation point. When soil moisture was considered it was noticed that high initial population in soil with 50% moisture produced 141.8 x 103 c.f.u. /g at 5 cm distance followed by soil with 75% moisture.